Study the Effect of the ultrasonic in the preparation of binary composites ZnO:AgO nanomaterials and its application in removal tetracycline : Studi tentang Pengaruh Gelombang Ultrasonik dalam Pembuatan Komposit Biner Nanomaterial ZnO:AgO dan Penerapannya dalam Penghilangan Tetrasiklin - Ahmed A. Ismail (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Nanostructured metal oxides have gained increasing attention due to their versatile applications in environmental remediation. Specific Background Zinc oxide-based nanomaterials, particularly when modified with silver, have been widely investigated for their photocatalytic properties under light irradiation. Knowledge Gap However, limitations remain in achieving efficient charge separation and improving photocatalytic performance under practical conditions. Aims This study aims to synthesize Ag-doped ZnO nanostructures and evaluate their structural, optical, and photocatalytic properties for dye degradation applications. Results The synthesized nanocomposites exhibit improved crystallinity, reduced particle size, and enhanced light absorption, leading to higher photocatalytic degradation efficiency compared to pure ZnO. Novelty The incorporation of silver into ZnO nanostructures provides a synergistic effect that optimizes photocatalytic activity through improved electron–hole separation mechanisms. Implications These findings contribute to the development of advanced nanomaterials for sustainable wastewater treatment and offer potential for broader environmental applications. Keywords: ZnO Nanostructures, Silver Doping, Photocatalysis, Dye Degradation, Nanocomposites Key Findings Highlights Ag incorporation modifies structural and optical behavior of ZnO materials Nanocomposites demonstrate superior degradation performance under light exposure Improved charge carrier dynamics observed in modified semiconductor systems